Safety evaluation of ondansetron after gestational exposure on male reproductive parameters in rats - Reis, Ana Carolina Casali [UNESP]; Jorge, Bárbara Campos [UNESP]; Stein, Julia [UNESP]; Moreira, Suyane da Silva [UNESP]; Manoel, Beatriz de Matos [UNESP]; Aquino, Ariana Musa [UNESP]; Valente, Leticia Cardoso; Kassuya, Cândida Aparecida Leite; Scarano, Wellerson Rodrigo [UNESP]; Arena, Arielle Cristina [UNESP] (Elsevier, 2023)
Ondansetron is a 5HT3 receptor antagonist widely used to treat hyperemesis gravidarum, although its safety is still questionable. Since 5HT3 receptors, which are the target of this drug, can interfere with brain development through changes in neurotransmitter levels, this study evaluated whether the prenatal exposure to this drug could compromise reproductive and behavioral parameters in male offspring. Pregnant rats were treated with ondansetron (1.7 and 2.5 mg/kg/body weight; gavage), from gestational day 1–21. No exposure-related changes in clinical signs, body weight, food consumption, pregnancy length, and necropsy findings were observed in dams. Ondansetron exposure did not alter the anogenital distance or age of preputial separation in male offspring. Similarly, males exposed to therapeutic doses of ondansetron did not exhibit changes in play behavior. In adulthood, there were no changes in sperm parameters, as well as in testosterone level, sexual behavior and fertility. Furthermore, ondansetron did not interfere with testicular and epididymal histology, and with androgen receptor expression in hypothalamus. In conclusion, prenatal exposure to ondansetron did not cause maternal toxicity, as well as did not interfere with reproductive parameters of male offspring, indicating its safety after gestational exposure in rats.
Keywords: 5HT3; Brain sexual differentiation; Hyperemesis gravidarum; Male rats; Pregnancy